Architecture Application Scheduling and Monitoring Improvements to Hull in PT. Tambangan Raya Permai - Zulkarami, Refi; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
The process of refinement the hull of a ship done by PT TAMBANGAN RAYA PERMAI so far bring up problems of lack of supervision and too long time to repairing project of the hull of a ship. Because of a lack of supervision and not scheduled structurally to repairing project of the hull of a ship so as to cause slowness repairing project of the hull of a ship. This problem will have an impact on time the process of refinement the hull of a ship which will be repaired. To solve the problem, then made an application scheduling and monitoring improvement the hull of a ship. In this research, application scheduling and monitoring improvement the hull of a ship is using network planning, where scheduling is expected to assist repairing project of the hull of a ship so can increase improvement the hull of a ship.Based on the results of the trial that has has been done, can be concluded that this program has been increase the performance of the process repairing project of the hull of a ship. This was apparent from supervision work and the process of being a scheduled well after using application of research.